Pelatihan Literasi Kesehatan Digital Bagi Kader Posyandu Untuk Deteksi Dini Penyakit Hipertensi Di Desa Kunduran Kecamatan Ulu Musi Kabupaten Empat Lawang - Hengki Tranado; Saputra , Fery Surahman; Juita, Rina; Habibi , Julius; Hidayat , Yance (STIA Bengkulu, 2026)
Hypertension is a non-communicable disease whose prevalence continues to increase globally and nationally. According to the World Health Organization (WHO), hypertension is a condition where systolic blood pressure reaches ≥140 mmHg and/or diastolic blood pressure ≥90 mmHg. It is known as a silent killer because it often has no symptoms in its early stages. According to the World Health Organization (WHO), by 2024, an estimated 1.4 billion adults aged 30–79 worldwide will suffer from hypertension, representing approximately 33% of the population in that age range. Based on the 2023 Indonesian Health Survey (SKI), the prevalence of hypertension among people aged 18 years and over reached 30.8%, indicating that nearly one-third of adults live with high blood pressure. According to the